Failure to demonstrate pluripotential hemopoietic stem cells in mouse brains. - Hoogerbrugge, P M (1985)
Hemopoietic stem cells as defined by the capacity to produce spleen colonies in lethally irradiated recipients were reported by P. F. Bartlett [(1982) Proc. Natl. Acad. Sci. USA 79, 2722-2725] to be present in high frequencies in mouse brain. He also reported similar numbers of colony-forming units, spleen (CFU-s), in the brains of Wf/Wf mice, the bone marrow of which lacks detectable spleen colony-forming cells. To verify these observations, single cell suspensions were produced from murine brains by incubation with trypsin and DNase, followed by removal of myelin by Percoll gradient centrifugation. Two to 13 CFU-s were detected per brain. This low number suggested contamination of the brains by either blood or bone marrow leaking from the skull bones during dissection. When the isolated, intact brains were washed carefully in balanced salt solution, the recovered number of CFU-s decreased to 0.1-0.4 per brain. No CFU-s could be detected in the brains of W/Wv mice. It is concluded that the CFU-s observed by Bartlett in preparations of mouse brain did not originate from the brain tissue.